The Development of Indonesia Environmental Performance and Environmental Compliance - Sofik Handoyo (Journal of Accounting Auditing and Business, 2018)
This study aims to analyze the development of Indonesia environmental performance and environmental compliance from the period 2011-2015 through the PROPER program. Statistic descriptive, along with trend analysis, was applied in this study. The result indicates that achievement of the environmental performance of the PROPER program is on adequate level (63,2%), Poor level (25,9%), good level (7,5%), very poor (2.8%) and excellent level (0.6%). Meanwhile, Indonesia environmental compliance level on average is 72%. There is still 28% of the PROPER participant not comply with environmental requirements determined by the Ministry of Environment (MOE). The achievement of environmental compliance consists of beyond compliance (12%) and adequate compliance (88%).